1993
DOI: 10.1080/00071669308417657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a soluble polysaccharide (carboxy methyl cellulose) on the physico‐chemical conditions in the gastrointestinal tract of broilers

Abstract: 1. The effects of an indigestible soluble polysaccharide (carboxy methyl cellulose: CMC) on broiler performance (body weight gain, food and water intake) and on chyme characteristics (moisture content, viscosity, pH, osmolality and retention time) in broilers were studied. 2. In semi-synthetic diets 0, 5.0 and 10.0 g/kg of cellulose was replaced by CMC on weight basis. These diets were fed to male broilers from 3 to 5 weeks of age. 3. When 10.0 g/kg CMC was included in the diet, food intake and body weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…The watery digesta and faeces for pigs fed the CMC diet indicated less water retention and the onset of diarrhoea, similar to the observation with weaned pigs fed a CMC diet or pearled barley (23 -25) , and the watery digesta was related to high digesta viscosity. The high digesta viscosity by inclusion of CMC in diets slows digesta passage rate and thereby creates a favourable environment for the proliferation of microbial pathogens (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The watery digesta and faeces for pigs fed the CMC diet indicated less water retention and the onset of diarrhoea, similar to the observation with weaned pigs fed a CMC diet or pearled barley (23 -25) , and the watery digesta was related to high digesta viscosity. The high digesta viscosity by inclusion of CMC in diets slows digesta passage rate and thereby creates a favourable environment for the proliferation of microbial pathogens (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in poor digestibility are not fully understood but it is recognized that viscosity reduces the intestinal passage rate (van der Klis et al, 1993), reduces the diffusion of digestive enzymes and stimulates bacterial proliferation in the small intestine (Choct, 2006;Rodriguez et al, 2012). Moreover, the water-holding capacity brought about by soluble NSP markedly influenced voluntary feed intake.…”
Section: Dietary Treatmentmentioning
confidence: 99%
“…These results are similar to those reported for broiler chickens by Barekatain et al (2013b), who found that inclusion of 10-30% sDDGS in diets significantly increased feed intake and the feed/gain ratio in broiler chickens from 1 to 35 days. DDGS consists of a greater proportion of soluble nonstarch polysaccharides (NSP) (28.6 g soluble NSP/kg dry matter, 184.9 g insoluble NSP/kg dry matter) than the respective native grains; the presence of NSP increases digesta viscosity (Smits and Annison, 1996) and reduces the feed passage rate (Van der Klis et al, 1993), leading to lower growth rates and a higher feed/gain ratio. By contrast, xylanase supplementation in broiler chicken diets containing 30% sDDGS can improve the feed conversion ratio (Barekatain et al, 2013a, b), implying that appropriate supplementation with NSP enzymes could be beneficial to the feed efficiency of poultry diets containing sDDGS.…”
Section: Effect Of Sddgs On Performance Of Geese Aged 35 To 70 Daysmentioning
confidence: 99%